Targeted Sequencing of Alzheimer Disease Genes in African Americans Implicates Novel Risk Variants - Logue, Mark W.; Lancour, Daniel; Farrell, John; Simkina, Irina; Fallin, M. Daniele; Lunetta, Kathryn L.; Farrer, Lindsay A. (Frontiers in Neuroscience, 2018)
The genetic architecture of late-onset Alzheimer disease (AD) in African Americans (AAs) differs from that in persons of European ancestry. In addition to APOE, genome-wide association studies (GWASs) of AD in AA samples have implicated ABCA7, COBL, and SLC10A2 as AA-AD risk genes. Previously, we identified by whole exome sequencing a small number of AA AD cases and subsequent genotyping in a large AA sample of AD cases and controls association of AD risk with a pair of rare missense variants in AKAP9. In this study, we performed targeted deep sequencing (including both introns and exons) of approximately 100 genes previously linked to AD or AD-related traits in an AA cohort of 489 AD cases and 472 controls to find novel AD risk variants. We observed association with an 11 base-pair frame-shift loss-of-function (LOF) variant in ABCA7 (rs567222111) for which the evidence was bolstered when combined with data from a replication AA cohort of 484 cases and 484 controls (OR=2.42, p=0.022). We also found association of AD with a rare 9 bp deletion (rs371245265) located very close to the AKAP9 transcription start site (rs371245265, OR=10.75, p=0.0053). The most significant findings were obtained with a rare protective variant in F5 (OR=0.053, p=6.40x10-5), a gene that was previously associated with a brain MRI measure of hippocampal atrophy, and two common variants in KIAA0196 (OR=1.51, p<8.6x10-5). Gene-based tests of aggregated rare variants yielded several nominally significant associations with KANSL1, CNN2, and TRIM35. Although no associations passed multiple test correction, our study adds to a body of literature demonstrating the utility of examining sequence data from multiple ethnic populations for discovery of new and impactful risk variants. Larger sample sizes will be needed to generate well-powered epidemiological investigations of rare variation and functional studies are essential for establishing the pathogenicity of variants identified by sequencing.